(untitled) (Research, Society and Development, 2021)
In this study, we proposed to verify the most suitable murine experimental model for studying human giardiasis. In total 150 animals were used. Fifty mice (Mus musculus) from each lineage (Swiss, Balb/c and C57BL/6), 25 females and 25 males, were divided into 5 groups with 5 animals each, according to the lineage/sex. Three groups were infected with 104 cysts of Giardia duodenalis of assemblage BIV and 2 negative control groups. The animals were followed and evaluated for 15 days after receiving the inoculum. The clinical parameters evaluated were body weight, water and feed intake, excretion, appearance of fur and feces, elimination of Giardia spp cysts and behavioral assessment. The clinical parameters of the groups infected with G. duodenalis were compared with the non-infected groups within their own lineage/sex. In the 15 days of monitoring, only the male Swiss mice presented differences in these parameters. The infected animals consumed more feed, water and eliminated more excreta than the non-infected group. There was no difference in the general average of the weight of the animals or in the behavioral assessment in any group. Only the infected male Swiss mice eliminated G. duodenalis cysts in the feces, which was confirmed by the molecular diagnosis and by observing the presence of trophozoites in the intestinal mucosa. The results demonstrate that the most suitable animal model for the study of human giardiasis is the male Swiss mice, since it was the only one capable of developing infection by G. duodenalis cysts.